Macrophage inflammatory protein‐3 alpha (MIP‐3a) Is a novel serum prognostic marker in patients with colorectal cancer1. Issue 2 (23rd August 2012) - Iwata, Takashi; Tanaka, Koji; Inoue, Yasuhiro; Toiyama, Yuji; Hiro, Junichiro; Fujikawa, Hiroyuki; Okugawa, Yoshinaga; Uchida, Keiichi; Mohri, Yasuhiko; Kusunoki, Masato
Abstract Background and Objectives A significant prognostic difference exists among metastatic colorectal cancer (CRC) patients despite of any treatments. We identify the specific cytokines related to prognosis of metastatic CRC and assess their prognostic significance. Methods Stage IV CRC patients were divided into two groups according to their prognosis. Difference in serum cytokine level between these groups was determined by the cytokine array. Among the specific cytokines, macrophage inflammatory protein‐3 alpha (MIP‐3a) was measured using an enzyme‐linked immunosorbent assay (ELISA) in the sera of 242 CRC patients. Results Several cytokines related to prognostic difference in stage IV CRC were identified. The median MIP‐3a level (28.2 pg/ml) was used as a cut‐off value. Increased MIP‐3a was significantly associated with synchronous liver metastases and age. In univariate analysis, high MIP‐3a was correlated with poor prognosis (P < 0.001). Multivariate analysis showed that high MIP‐3a was an independent prognostic factor in all CRC patients (P < 0.001). In subgroup analysis, high MIP‐3a was significantly associated with poor survival in patients with stage II, II/III, and IV CRC, respectively. Conclusions Serum MIP‐3a is not only an independent prognostic factor, but also an independent predictive factor for liver metastasis, which may guide the decision making of metastatic CRC patients. J. Surg. Oncol. 2013;107:160–166. © 2012 Wiley Periodicals, Inc.